2022
DOI: 10.1101/2022.10.10.510913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of dual pharmacological correction and potentiation of human CFTR

Abstract: Cystic fibrosis (CF) is caused by mutations in a chloride channel called the human Cystic Fibrosis Transmembrane Conductance Regulator (hCFTR). We used cryo-EM global conformational ensemble reconstruction to characterize the mechanism by which the breakthrough drug VX445 (Elexacaftor) simultaneously corrects both protein-folding and channel-gating defects caused by CF mutations. VX445 drives hCFTR molecules harboring the gating-defective G551D mutation towards the open-channel conformation by binding to a sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 68 publications
5
14
0
Order By: Relevance
“…8e,f). In agreement with these data, the findings of a recent cryo-EM study showed that the G551D variant adopts conformations in between those of the fully NBD-separated and NBD-dimerized conformations 33 .…”
Section: Disease Mutations Disrupt Allosteric Couplingsupporting
confidence: 68%
See 1 more Smart Citation
“…8e,f). In agreement with these data, the findings of a recent cryo-EM study showed that the G551D variant adopts conformations in between those of the fully NBD-separated and NBD-dimerized conformations 33 .…”
Section: Disease Mutations Disrupt Allosteric Couplingsupporting
confidence: 68%
“…4b,g). This observation, together with the recent cryo-EM study of the CFTR(G551D) variant in the presence of ivacaftor 33 , demonstrates that neither ivacaftor nor GLPG1837 promotes NBD dimerization. Similarly, for the L927P variant, the relative stimulation of open probability greatly exceeded the relative stimulation of dimerization probability (Fig.…”
Section: Potentiators Promote Opening Of Dimerized Channelsmentioning
confidence: 73%
“…1c and Supplementary Table 1) 8,47 . Combination of VX-809 with the VX-445 corrector, which targets the TMD2(TMH10-11) and the N-terminal Lasso segment 15,17 , restored WT-like folding efficiency (∼36%) of ΔF508-CFTR (Fig. 1c), consistent with the mutant steady-state cellular accumulation based on functional studies 14 .…”
Section: Resultssupporting
confidence: 64%
“…The CFTR cooperative domain-folding model dictates that following the formation of secondary and some tertiary structural elements co-translationally, the native domain-swapped conformational ensembles develop posttranslationally 15 , which requires dynamic and/or energetic interdomain coupling and the expression of the full-length CFTR or its minimal folding unit (TMD1-NBD1-RD- TMD2 or CFTR-ΔNBD2) 8,27 . The cooperative folding model aligns with the observation that the correctors binding sites overlap with the WT-CFTR conformational poses in the cryo-EM structures, 15,17 suggesting that conformers can accumulate synchronously with the posttranslational development of permissive inter-domain interactions. The intrinsically unstructured regulatory (R) domain (Supplementary Fig.1a) was found to be dispensable for CFTR expression 28 .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation